ANALYSIS OF HEALTH SERVICES QUALITY FOR PREGNANT WOMEN IN HEALTH CENTERS COMMUNITY (PUSKESMAS) NGALIYAN, SEMARANG CITY - Amelia, Arini Rizky; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2019)
Ngaliyan Sub-district has an emergency handling of Maternal Mortality Rate (MMR), it is also has red zone of MMR in Semarang city for the last 3 years. The problem became background why researcher conducts this research. The aim of this research was analyzing health services quality for pregnant women in Community Health Centers (Puskesmas) Ngaliyan. Not only that, this research also aimed at describing and analyzing obstacle factors of health services quality for pregnant women in Community Health Centers Ngaliyan. This research was using services quality theory by Zeithmal, it uses some criteria such as Tangible, Reliability, Responsiveness, Assurance, and Empathy. Qualitative research was used in this study as well. Interview, observation, and documentation were used to collect the data. The informants were selected purposively. The result of this research shows that Tangible, Reliability, and Empathy criteria have not fully done well. The obstacle factor of health services quality for pregnant women are number crisis and competence of existing human resources, un-efficient services, a passive and undisciplined society. Some recommendations are given as follows; implementation steps of human resource development in effective ways, alignment of relations between the government with UPTD Community Health Centers (Puskesmas) Ngaliyan, and the last socialization and education about the needs to oversee the performance of UPTD to the community.